Implementasi Teknik Role play dengan Project-Based Learning untuk Meningkatkan Keterampilan Listening dan Speaking Pada Mata Kuliah Bahasa Inggris II - Handayani, Reli; Ernanda, Ernanda (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2024)
This study described the implementation of role-play in enhancing listening and speaking skills using PjBL in the English II course. Through a qualitative descriptive approach where the researcher acts as an observer and participant in the classroom, this study indicated that the role-play technique allows students to use English in real-life situations actively. Students can enhance their listening and speaking skills, boost their confidence in communication, and practice teamwork and collaboration within the groups. The project-based role-play makes language learning more relevant and authentic. These insights could shape the future EFL/ESL teaching techniques by emphasizing the transformative role of project-based role-play techniques in language education. By integrating such techniques into their pedagogical practices, language teachers can create dynamic learning environments that foster comprehensive language acquisition.